Auld Lang Syne - Grant, M. J. (Open Book Publishers, 2021)
In Auld Lang Syne: A Song and its Culture, M. J. Grant explores the history of this iconic song, demonstrating how its association with ideas of fellowship, friendship and sociality has enabled it to become so significant for such a wide range of individuals and communities around the world.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books